Heritage of Cyador - Modesitt, L. E., Jr., 1943- (Modesitt, L. E., Jr., 1943- Saga of Recluce., 2014)
Cigoerne's Mirror Lances commander Lerial leads three troops on a mission to protect Afrit and Cigoerne from a Heldya invasion, an effort that is complicated by Lerial's troubled past.